Grouped caging predisposes male mice to ankylosing enthesopathy. Issue 9 (September 1996) - Weinreich, S; Capkova, J; Hoebe-Hewryk, B; Boog, C; Ivanyi, P
Abstract : OBJECTIVE: To evaluate the number of males per cage as a possible risk factor for murine ankylosing enthesopathy (ANKENT)--a spontaneous joint disease with parallels to human seronegative spondylarthropathies--since ANKENT shows incomplete penetrance of genetic susceptibility factors among individuals living in a stable environment. METHODS: Frequency of ANKENT was compared among males housed with females, with other males, or alone. RESULTS: In three independent cohorts, a trend was observed that males housed with females rarely develop the disease, in contrast to males housed with other males (P < 0.25, P < 0.05, and P < 0.01). Furthermore, no males caged alone developed ANKENT, whereas disease did occur in males grouped together (P < 0.01). When healthy males (retired breeders) were recaged either alone or with other males, ANKENT developed among the grouped males only (P < 0.005). CONCLUSIONS: Caging males together is a relative risk factor for ANKENT. Grouped caging may perturb the immune system through endocrine pathways or modify microbiological load through behaviour (for example, infection due to biting).